(untitled) (Constructionism Conference Proceedings, 2025)
This contribution provides an overview of MathsBeat, an interdisciplinary constructionist learning activity designed to engage primary pupils with digital and physical artefacts through rhythm-based composition activities and interactive coding exercises. Framed within a Design-Based Research methodology (Barab & Squire, 2004), we present insights from iterative classroom implementations and practitioner feedback to explore how interdisciplinary tasks can bridge mathematics, music, movement and computational thinking. Our goal with the design of this activity is to engage primary school students with their mental models relating to bodily movement, musical timings, mathematics and computational thinking to capture something they find fascinating – potentially reducing stereotypical views of mathematics as a purely formal domain. Our overarching question during this DBR phase is how students’ and teachers’ experiences MathsBeat inform its iterative design and their views on its potential as an interdisciplinary activity.